This Pendekatan Individu dan Pendekatan Interaksi dalam Mengatasi Masalah Pendidikan di Sekolah - Wati, Oktia; Tutuk, Ningsih (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research aims to overcome educational problems in schools through an individual approach and an interaction approach. The research uses a qualitative method based on library research with primary sources from books, while secondary sources come from journal articles and other scientific works. Data analysis techniques are carried out starting from data collection, data reduction, data presentation, and conclusions (Milles and Huberman). This research argues that the individual approach pays attention to students' personal aspects such as character, psychology and psychomotor abilities to understand students' biological, psychological and psychomotor factors to understand the specific problems students face as well as an interaction approach to improve students' abilities in interacting with the environment. Educational problems are caused by internal and external factors, student interactions with teachers, students and the environment. Apart from that, the implementation of the sociological approach to education is carried out through an individual approach including inclusion programs, guidance and counseling, remedial teaching, character strengthening. Meanwhile, the interaction approach is carried out through small groups and the teacher's role as facilitator.